2011
DOI: 10.1007/s10165-011-0446-3
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking in primary Sjögren’s syndrome: positive association only with ANA positivity

Abstract: Smoking is well known to contribute to the pathogenesis and severity of some systemic autoimmune rheumatic diseases and especially to the production of certain autoantibodies. Primary Sjögren's syndrome (pSS) is an autoimmune disease, affecting primarily the exocrine glands. It may also cause extraglandular involvement in some cases. In this study, we aimed to determine the frequency of smoking habits in our cohort of pSS patients and to investigate whether the frequencies of autoantibody positivity and extrag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 16 publications
4
21
1
Order By: Relevance
“…Our study found no significant relationship between ANA positivity by immunofluorescence nor by luminex bead-based assay and smoking status, contrary to a previous study which found an association in Sjogren’s syndrome 8 . While there were different levels of ANA positivity between our subjects with SLE, our unaffected FDRs and our healthy controls, there were no significant differences by smoking status in the proportion of individuals positive for ANA in any of these groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study found no significant relationship between ANA positivity by immunofluorescence nor by luminex bead-based assay and smoking status, contrary to a previous study which found an association in Sjogren’s syndrome 8 . While there were different levels of ANA positivity between our subjects with SLE, our unaffected FDRs and our healthy controls, there were no significant differences by smoking status in the proportion of individuals positive for ANA in any of these groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Smoking has also been associated with seropositivity for SLE-related autoantibodies, including anti-dsDNA in individuals with SLE 7 , and ANA in primary Sjogren’s syndrome 8 . In addition, smoking appears to play a role in autoantibody positivity in other autoimmune diseases, namely rheumatoid arthritis (RA) 919 .…”
Section: Introductionmentioning
confidence: 99%
“…The associations observed could be due to secondary effects on the digestive tract of the diseases, or their treatment, and do not necessarily mean a common causal aetiology [1]. Smoking per se is associated with a higher prevalence of ANA [30], and this could explain the higher ANA positivity in our study with a high frequency of former and current smokers. Thus, our finding in the present study does not indicate that auto-immunity is the most important cause of MC.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, it has been found that ANA titres correlate with the number of positive autoantibodies against specific nuclear antigens, as well as with the percentage and levels of serum gammaglobulins [5,24]. Finally, a cross-sectional study from Turkey, including 207 pSS patients and 602 healthy controls, suggested an association of smoking with ANA positivity in the SS group [44].…”
Section: Clinical Implications Of Anti-ro/ssa and Anti-la/ssb In Sjögmentioning
confidence: 96%